ROOFER: A Management Tool for Maintaining Built-Up Roofs - Bailey, David M.; Brotherson, Donald E.; Tobiasson, Wayne (1989)
This paper describes ROOFER, a roofing maintenance management system for built-up roofs being developed by the U.S. Army Construction Engineering Research Laboratory with the assistance of the U.S. Army Cold Regions Research and Engineering Laboratory and the U.S. Army Engineering and Housing Support Center. ROOFER provides building managers with a practical tool for evaluating built-up roofs, determining maintenance priorities, and selecting repair strategies that ensure the maximum return on investment. ROOFER comprises procedures for dividing the building roof into manageable sections, collecting and managing inventory information, inspecting and evaluating condition, and managing networks and projects. This paper is reprinted with permission from the Proceedings of the 9th Conference on Roofing Technology, 'Putting Roofing Technology to Work,' May 4-5, 1989, Gaithersburg, Maryland.